Different sensitivity to heatwaves across the life cycle of fish reflects phenotypic adaptation to environmental niche. (December 2020) - Madeira, Diana; Madeira, Carolina; Costa, Pedro M.; Vinagre, Catarina; Pörtner, Hans-Otto; Diniz, Mário S.
Abstract: Predicting responses of marine organisms to global change requires eco-physiological assessments across the complex life cycles of species. Here, we experimentally tested the vulnerability of a demersal temperate fish ( Sparus aurata ) to long-lasting heatwaves, on larval, juvenile and adult life-stages. Fish were exposed to simulated coastal (18 °C), estuarine (24 °C) summer temperatures, and heatwave conditions (30 °C) and their physiological responses were assessed based on cellular stress response biomarkers (heat shock protein 70 kDa, ubiquitin, antioxidant enzymes, lipid peroxidation) and phenotypic measures (histopathology, condition and mortality). Life-stage vulnerability can be ranked as larvae > adults > juveniles, based on mortality, tissue pathology and the capacity to employ cellular stress responses, reflecting the different environmental niches of each life stage. While larvae lacked acclimation capacity, which resulted in damage to tissues and elevated mortality, juveniles coped well with elevated temperature. The rapid induction of cytoprotective proteins maintained the integrity of vital organs in juveniles, suggesting adaptive phenotypic plasticity in coastal and estuarine waters. Adults displayed lower plasticity to heatwaves as they transition to deeper habitats for maturation, showing tissue damage in brain, liver and muscle. Life cycle closure of sea breams in coastal habitats will therefore be determined by larval and adult stages. Graphical abstract: Image 1 Highlights: Life-cycle assessments are crucial to forecast global change impacts on biota. Heatwave effects were tested in seabreams across their life cycle. Sub-cellular, cellular and whole organism indicators were assessed. The vulnerability of life cycle stages can be ranked as larvae > adults > juveniles. Life-cycle closure may be in jeopardy due to the sensitivity of larvae to heat.